Experiência de docentes em formação: desafios na docência e na vida - PEREIRA, Marciley Mesquita (2023)
The present work concerns the experience reports of teacher-students of the pedagogy course offered by the National Plan for Education Teachers (PARFOR), from the Federal University of Pará. The aim was to clarify the path training course of five student-teachers highlighting the challenges, lessons learned, experienced during the course, highlighting the arduous task of studying and working alongside Same time. For this, it was adopted the collection of the reports of the professors and students concomitant to the study and theoretical deepening, both helped us in the description of the experiences mediated by the theoretical basis. based on readings, in our own experience and that of other student-teachers it was possible to verify that the challenges were constant, of different nature and fundamental for the academic success of student-teachers in terms of learning/knowing how to reconcile life academic, personal and professional. Despite the challenges, what stands out most on this journey is the professional growth acquired through the articulation of the theory learned in the course and the practice caused by the teaching work.